Novel compounds from natural products in the new millennium : potential and challenges - Tan, Benny K-H (World Scientific, 2004)
There is continuing interest in natural products as sources of potentially new and exciting chemical compounds. This book brings together the knowledge, perspectives and research findings of a varied group of scientists on a wide range of topics, from microarrays, genetics and bioinformatics to yeast-based technologies and enzyme studies. Scientists and clinicians in life science research will find useful information on new research techniques and tools. For the agriculturist, there is interesting information on the potential and problems of natural-based pesticides. The cancer researcher will find several plant sources with potential anti-cancer and immunomodulating compounds, as well as a report on two new modalities in cancer therapy -- photosensitization with hypericin and immunotherapy. Latest developments of Chinese herbal extracts reported in this book may offer a new alternative therapy in the treatment of cardiovascular diseases. In addition, the later chapters awaken the would-be entrepreneur to the opportunities and challenges of research and development in the natural product industry, with the concluding chapter providing helpful insights into Intellectual Property Law.